TRENDS IN MODERN GLOBALIZATION - K. S. Dallakyan (Финансы: теория и практика, 2017)
The history of mankind since ancient times is characterized by trends on a global scale. Modern globalization processes have their origins in the 1960s, and the turning point in their development was the fall of the “socialist camp”. The nature, essence and content of globalization cause criticism and concern of scholars and experts, civil society activists. This fact signals the lack of knowledge and proves the need for further research. The author argues that globalization is a complex structural transformation, and its main objective trends are materialized in the occurrence of proper events; thus allowing to more or less successfully assess a cause and effect relationship. The article concludes that the agents as well as all participants of the globalization processes increasingly demonstrate the desire to accumulate, strengthen and enrich their economic, political and legal powers and authorities. Their substantial properties as well as the system-building function which defines social order are qualitatively predetermined by targeted globalization effects where the key role is played by the Kantian notion of “self-regard”. Keywords: globalization; trend of globalization; social philosophy; post-industrial society.